Pelatihan Pembuatan Media Pembelajaran Berbasis AutoPlay bagi Kelompok Kerja Guru Kecamatan Geger di Kabupaten Bangkalan - Buaddin Hasan; Didik Hermanto (Universitas Prof. Dr. Hazairin, SH, 2019)
Training on Creating AutoPlay Based Learning Media for Teacher Working Groups in Geger District, Bangkalan Regency Media becomes a tool that is needed by educators to create a pleasant atmosphere of a learning process. In the learning process, teachers should use interactive media as a medium for delivering information. Media in the learning process is intended to facilitate the teacher in conveying messages, information, or subject matter to students. This service program was aimed to provide mentoring to teachers in creating interactive learning media based on AutoPlay. This service program is carried out by two methods. The first was the public education method, namely training and mentoring for teachers in creating learning media with various applications, especially AutoPlay. This training method was an effort to educate and train partners to be able to use computers to produce exciting learning media. The second was the substitution of a science-and-technology method, which provided an overview of how to use technology in making learning media. The result of the implementation of this service was an increase in the knowledge and skills of teachers, reaching 90% of the 20 teachers who participated in the service program. On average, 80% of teachers were able to implement AutoPlay media in the learning process. The use of AutoPlay media in learning made students more motivated in learning.